Alien freshwater fish species in the Balkans—Vectors and pathways of introduction. Issue 1 (23rd August 2017) - Piria, Marina; Simonović, Predrag; Kalogianni, Eleni; Vardakas, Leonidas; Koutsikos, Nicholas; Zanella, Davor; Ristovska, Milica; Apostolou, Apostolos; Adrović, Avdul; Mrdak, Danilo; Tarkan, Ali Serhan; Milošević, Dragana; et al.
Abstract: Fish introductions, particularly in areas of high biological diversity and endemism, represent a major threat for biodiversity. In the Balkan Peninsula, 60 fish species have been introduced to date, of which 36 have become naturalized in inland waters. Since the Balkans are one of the world's 35 biodiversity hot spots, this large presence of alien fish species poses a serious threat for the stability of freshwater ecosystems and the survival of the native ichthyofauna and of aquatic biodiversity in general. The motivation for the introductions, and the historical timeline, varies among the Balkan states. Despite recent attempts to implement and align legislation aimed at preventing the introduction of potentially invasive species, and the implementation of rigorous controls of introductions and increased protection of open waters, the majority of current introductions remain intentional, primarily via aquaculture. This review article provides a historical overview of freshwater fish introductions, the motivation behind them and the current distribution of alien freshwater fishes in the Balkans. The ecological implications and future perspectives concerning alien fish species in the region are also discussed.